“Meth Circles” and “Pipe Pirates”: Crystal Methamphetamine Smoking and Identity Management Among a Social Network of Young Adults - Green, Rachael; Moore, David (Informa Healthcare, 2013)
This article analyzes crystal methamphetamine smoking among a social network of young Australian adults. Ethnographic data were collected from 2005 to 2007among 60 individuals, and semistructured in-depth interviews were conducted with a sub-set of 25 individuals. Fieldnotes and interview transcripts were entered intoNVivo7 and thematically analyzed. We argue that although drug use may be considered “normal” among some social networks, the management of stigma associated with drug use is more complex and contested than portrayed in the literature. Policy implications are discussed. The study was supported by funds from Australia’s National Health and Medical Research Council.